New methods of normative monetary evaluation of agricultural lands: positive and negative aspects - Tretiak, A.; Tretiak, V.; Kovalyshyn, O.; Kryshenyk, N. (Land Management, Cadastre and Land Monitoring, 2017)
Approaches to the normative monetary evaluation of agricultural lands, adopted by the resolution of the Cabinet of Ministers of Ukraine dated March 23, 1995 No. 213, did not allow to accomplish objective actualization of the indicators, as they did not take into account changes in the economy and the system of agricultural land use that occurred during the implementation of land reform in agriculture. So there is no doubt of the necessity to take into consideration the   changes and to improve methodical approaches to the evaluation of agricultural land.The resolution of the Cabinet of Ministers of Ukraine dated November 16, 2016 No. 831 adopted the updated "Methodology of normative monetary evaluation of agricultural lands ".According to the paragraph 3 of the methodology, normative monetary evaluation of agricultural lands  is determined in accordance with the requirements of capitalized rental income for agricultural lands of natural and agricultural districts of the Autonomous Republic of Crimea, regions, cities of Kiev and Sevastopol in accordance with the Annex and indicators of soil evaluation by drawing up scales of normative monetary evaluation of agricultural industrial groups of soils of natural and agricultural areas (for farmlands).The first question that arises regarding the updated methods is a natural-agricultural zoning. In fact, in this methodology there is no list of borders, natural agricultural areas in the section of the territories of village councils and settlements included in one or another area. If we use the map of the natural-agricultural zoning and the reference book to it proposed for consideration by the site of State Geocadaster of Diagrams, it contains other boundaries, and another list of village councils, settlements, for example in the section of the mentioned Radekhiv district, than the natural-agricultural zoning was previously approved. So, one of them combines 29, and others combine 2 village councils each. This reference book does not have a column regarding the name of the natural-agricultural district. It is therefore difficult to determine any areas classified as village councils as well as settlements.Analyzing data concerning the evaluation of agricultural lands according to the old and new methods it was determined that the value of arable land in the study area decreased overall by more than 7 thousand UAH but in some areas of councils - almost by 2 times. Such a decrease in the value of land is not logical, because the production of agricultural products during 1995-2001 inthe district did not diminished, but rather increased.New methods of normative monetary evaluation of agricultural lands for proving the objectivity of the results, requires grounding of information regarding the determination of the boundaries of natural-agricultural regions and objectivity of differentiation of indicators of capitalized rental income from the general (in Ukraine) to partial one (the land plot).Key words: normative monetary evaluation of agricultural land, natural and agricultural zoning, capitalized rental income.